2013
DOI: 10.1007/s12639-013-0383-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of endoparasitic infections of non descript dogs in Mathura, Uttar Pradesh

Abstract: The objective of this study was to investigate, through cross-sectional survey, the distribution, types and prevalence of gastro-intestinal parasites affecting stray dogs in and around Mathura, India. Freshly voided faecal samples of 108 identified, stray, non descript dogs of either sex and different age groups were collected and examined for coprological examination by direct faecal smear method; simple flotation and sedimentation techniques to detect parasitic oocysts and/or eggs. A total of 96 samples (88.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
3
13
1
Order By: Relevance
“…Moreover, since 2006 in Warsaw they are obligated to clean up after their dogs, that might protect the environment against spreading of parasite infections. Both in dogs and cats the eggs of roundworms were identified more often in young animals than in older ones, which is in line with the results obtained in previous epidemiological studies on the prevalence of the nematodes of the genus Toxocara, and it seems obvious that this observation results from intrauterine and lactogenic route of infection (5,9,30,32,34,38). Correlations between toxocarosis and the sex of the animals were observed in both dogs and cats, but they were statistically insignificant.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, since 2006 in Warsaw they are obligated to clean up after their dogs, that might protect the environment against spreading of parasite infections. Both in dogs and cats the eggs of roundworms were identified more often in young animals than in older ones, which is in line with the results obtained in previous epidemiological studies on the prevalence of the nematodes of the genus Toxocara, and it seems obvious that this observation results from intrauterine and lactogenic route of infection (5,9,30,32,34,38). Correlations between toxocarosis and the sex of the animals were observed in both dogs and cats, but they were statistically insignificant.…”
Section: Resultssupporting
confidence: 89%
“…This trend likely reflects an increased awareness among dog owners about parasitic diseases, increased use of deworming and preventative protocols, and the improved efficacy of new products on the market (Palmer et al, 2010). The odds of being positive for parasites decreased by 4% each year, which is in agreement with other studies (Barutzki and Schaper, 2013;Sudan et al, 2015;Tamponi et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…According to some studies, monoparasitism appears to be much more common than polyparasitism in pets presented to a teaching hospital (Kirkpatrick, 1988;Sudan et al, 2015), monoparasitism (38.1%) was less frequent than polyparasitism (46.7%). Additionally, the low socio-economic conditions can affect the host-parasite relationship, leading to more pet scavenging for food and therefore more parasite exposure (Schurer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A significantly high proportion of young dogs were infected with Ancylostoma caninum, Toxocara canis and Cystoisospora sp. Some age-dependent analyses have shown that puppies are more susceptible to these intestinal parasites than adult dogs [6,26]. Particularly, younger dogs are more exposed to Toxocara canis and Ancylostoma caninum infections because they can acquire these helminths by several routes such as transmammary routes by migrating larvae, ingestion of embryonated eggs from the environment or finally by somatic larvae via paratenic hosts [6].…”
Section: Discussionmentioning
confidence: 99%